Influencia del nivel de motivación y actitud en el rendimiento académico de los estudiantes del segundo nivel de la Facultad de Ciencias de la Educación y Humanidades de la Universidad Nacional de la Amazonía Peruana 2023 - Gaslac Galoc, Rodolfo (2025)
The research is quantitative, observational, prospective, analytical, explanatory and of causal correlational design, and was carried out with the purpose of explaining to what extent the level of motivation and attitudes towards the professional career influence the academic performance of students; 233 students of the second level of the different study programs offered by the Faculty of Education participated in the study; to collect the information of the variables motivation and attitudes, surveys were used through questionnaires measured by the Likert scale and for the variable academic performance, the Record of Proceedings provided by the Academic Affairs Registration Office was reviewed. The Main Hypothesis was formulated: The level of motivation and attitudes towards the professional career influence students' academic performance. The logistic regression model shows that neither motivation nor career attitudes have a statistically significant influence on the academic performance of second level students. And, given this reality, it is essential that subsequent educational strategies consider other factors, such as teaching quality and academic environment to improve academic performance.